CO-INTEGRATION DAN CONTAGION EFFECT ANTARA INDEKS SAHAM SYARIAH DI BEBERAPA NEGARA DAN JAKARTA ISLAMIC INDEX (JII) PADA PERIODE KRISIS YUNANI - Ardana, Yudhistira (Jurnal Manajemen Magister Darmajaya, 2017)
This research aims to analyze cointegration of sharia market share in Indonesia, Malaysia, US, Canada, UK, Japan, Europe and Asia-Pasific at the period of Greece crisis. Moreover, this research is also to find the most dominant countries which influence to volatility of sharia market share in Indonesia at the period of Greece crisis. Besides this research is to analyze the contagion effect in sharia market share in others country sampled in this research. The data used in this research is secondary data, it is from weekly market share closing from 2007-2014. In processing data, the writer will divide into 2 periods namely before crisis and at the period of crisis. The period before crisis is begun from May 2007 until April 2010.While the period of crisis is begun from May 2010 until January 2014. The analysis method used is vector error correction model (VECM) and Innovation accounting in impulse response function (IRF) and forecasting error variance decomposition (FEVD).Keyword: Co-Integration, Contagion Effect, Stock Index